The reality of urban growth and its spatial implications for Algeria’s major cities -Constantine case study- - Debbache, Rabiaa (Journal of Human Sciences, 2021)
The high concentration of the population and the excellent position of the lower Sidi Mabrouk district in the metropolitan area of Constantine, as well as other main factors, including socio-economic factors, social culture and the marginalization of the citizen in the decision-making as to the space in which we live, have contributed to serious impacts on the urban fabric of the district, the deformation of its general aspect, also the lack of harmony and balance between its various components (habitat - inhabitants and equipment ... ) In our research, we studied the impact of urban growth on the urban fabric, given its critical importance, especially at the moment, because we are living in spatial anarchy, mainly due to the absence of the role of civil society in raising citizens’ awareness, their sense of belonging to it and the absence of motivation of the State, that is does not encourage the participation of citizens in decision-making and therefore in urban development.